Personal vision: enhancing work engagement and the retention of women in the engineering profession - Buse, Kathleen R.; Bilimoria, Diana (Frontiers in Psychology, 2014)
This study examines how personal vision enhances work engagement and the retention of women in the engineering profession. Using a mixed method approach to understand the factors related to the retention of women in the engineering profession, we first interviewed women who persisted and women who opted out of the profession (Buse & Bilimoria, 2014). In these rich stories we found that women who persisted had a personal vision that included their profession, and that this personal vision enabled them to overcome the bias, barriers and discrimination in the engineering workplace. To validate this finding on a larger population, we developed a scale to measure one’s personal vision conceptualized as the ideal self (Boyatzis & Akrivou, 2006). The measure was tested in a pilot study and then used in a study of 495 women with engineering degrees. The findings validate that the ideal self is comprised of self efficacy, hope, optimism and core identity. For these women the ideal self directly impacts work engagement and work engagement directly impacts career commitment to engineering. The findings add to extant theory related to the role of personal vision and intentional change theory. From a practical perspective these findings will aid efforts to retain women in engineering and other STEM professions.